The 5th Annual Shanghai Symposium on Clinical & Pharmaceutical Solutions through Analysis. (September 2014) - Zhang, Tianyi (Tee); Huang, Mike-Qingtao; Weng, Naidong; Zhang, Jeff; Lee, Mike
The 5th Annual Shanghai Symposium on Clinical & Pharmaceutical Solutions through Analysis (CPSA Shanghai 2014) was held on 16–19 April 2014 in Shanghai, China. The meeting featured highly interactive events including diversified symposia, roundtable discussions, workshops, poster sessions and conference awards. There were over 220 participants from more than 10 countries, with 45 oral presentations and 42 posters presented. In addition, the meeting included one preconference workshop and a joint session with local bioanalytical and drug metabolism discussion groups.